Elsevier's integrated pharmacology - Kester, Mark ... [et al.] (Mosby/Elsevier, 2007)
The content of this book deals with integration, essential for the study of pharmacology. Practitioners must consider mechanisms of action, adverse effects, and contraindications for any giveb drug to ensure proper and safe use by patients. Crucial to the considerrations is a thorough understanding of the biochemistry, physiology, and anatomy of the targets effected by the drug. The authors of the book describes mechnisms of action for a drug, adverse effects, and discuss potential drug interactions with other drugs or complementary alternative medicines.